Narratives of Feminism among Gen Z Filipino Women - Alvior, Carmela; Perez, Vanessa Mae; Generaga, Haidee; Labio, Monica (Journal of Interdisciplinary Perspectives, 2025)
Research on Gen Z women's perspectives on modern feminism is scarce in the Philippines despite its unique patriarchal culture. This study fills the gap by exploring how Filipino Gen Z women navigate work and family dynamics through a feminist lens. Using a phenomenological descriptive approach, the research involved fourteen (n=14) co-researchers in Bacoor, Cavite, aged 20–26. Data were collected through semi-structured online interviews, selected via snowball sampling. A combination of latent narrative and thematic analysis was employed to analyze the responses. The findings reveal that Gen Z Filipino women perceive modern feminism as central to promoting (1) gender equality and inclusivity and (2) women's empowerment and autonomy. However, they face significant challenges, including (3) enduring stereotypes and (4) societal and cultural expectations that hinder the full realization of feminist ideals. Despite these barriers, respondents view feminism as (5) a transformative force capable of reshaping societal norms and advancing genuine gender equality. This study contributes to the understanding of how global feminist ideals intersect with local traditions in the Philippines, offering insights that may inform policies and initiatives aimed at fostering gender equality in culturally conservative contexts.